Environmental science : active learning laboratories and applied problem sets. - Wagner, Travis, ....-; Sanford, Robert, ....- (Hoboken : Wiley, 2010)
One of the few lab books available in the field, Environmental Science is designed to provide environmental scientists with active learning situations that demonstrate the impacts of interactions between humans and the environment. It encourages readers to reflect on real life conditions and the connection to the environment and sustainability. Emphasis is placed on writing and communication through lab reports, presentations, and real-world scenarios. Environmental scientists will be able to apply concepts in the lab and gain a stronger understanding of the field.
Keywords: Milieukunde